KAJIAN PEMAHAMAN MASYARAKAT TERHADAP PERUBAHAN IKLIM DI KAWASAN PESISIR KECAMATAN PARIAMAN UTARA - Mohd Abi Rafdi; wiwandari Handayani (Teknik PWK (Perencanaan Wilayah Kota), 2016)
Climate change has been emerging as a phenomenal issue scientific research has found that climate change leads to serious global threat. One of the affected area because of climate change is Coastal area of Pariaman Utara. Coastal area of Pariaman Utara is potentially at risk. People has been living there for a long time hereditarily. Various condition of the community such as the education level, profession, etc. certainly affect community’s comprehension about climate change especially in Pariaman Utara District coastal area. This is caused by the lack of information and awareness of the community itself. This research aims to example the  Pariaman Utara District’s community comprehension climate change in coastal area. This research used mix-methods. Data collection done by questionnaire, observation and interview. Analysis used is statistic descriptive and cross-tabs. Examining community’s opinion by finding relation between community responses and it’s understanding about climate change in coastal area. Based on the research, obtained four categories that represent community’s understanding about climate change in coastal area. The results show that the third category, the people who didn’t undersand the reasons of climate change but did the proper actions dominate about 45% . Proper action of community initiated by government. Based on analysis, community comprehension about climate change refers to natural cycles.